The bachelor and the bride - Eden, Sarah M. (Proper romance., 2022)
"London,1866 - Dr. Barnabus Milligan has always felt called to help people, whether that means setting a broken bone or rescuing the impoverished women of London from their desperate lives on the streets as part of his work with the Dread Penny Society.Three years ago, he helped rescue Gemma Kincaid by marrying her in secret to protect her from her family, notorious grave robbers who were intent on keeping her working in the trade. But their unconventional relationship is nearly over before it begins when, six months after they exchange vows, Gemma realizes her love for Barnabus is unrequited. To protect her heart, she leaves, telling Barnabus to contact her if his feelings for her ever grow beyond a sense of duty. When Gemma finally receives a letter from Barnabus, inviting her to return home, she hopes to find a true connection between them. But she quickly learns that he only wants her help to foil the Kincaids, who have been terrorizing the boroughs of London, eager to gain both money and power. Heartbroken once more, Gemma agrees to help, but she warns Barnabus that she will not stay for long, and once she goes, he'll never see her again. Yet as the couple follow the clues that seem to connect the Kincaids to the Mastiff, the leader of London's underground criminal network, Gemma and Barnabus both realize they might make a better match than either of them suspected. Perhaps the marriage that had once saved Gemma's life, might prove the means of saving Barnabus--and his lonely heart--as well. But before the once-confirmed bachelor can properly court his secret bride, they'll need to evade the dangerous forces that are drawing ever closer to the hopeful lovers and the entire Dread Penny Society itself"--